Autophagy dysfunction in lysosomal storage disorders - Settembre, Carmine (Henry Stewart Talks, 2019)
Overview of the lysosome and autophagy, Lysosomal storage disorders (LSDs), Lysosomal vacuolization, Accumulation of LC3+ vesicles, Studying co-localization of Lamp1 with LC3 and p62, LC3-tandem assay to study AV-lysosome fusion, mTORC1 inhibitors and AV-lysosome fusion, Pharmacological modulation of autophagy